Adsorptive removal of 1-naphthol from water with Zeolitic imidazolate framework-67. (August 2017) - Yan, Xinlong; Hu, Xiaoyan; Chen, Tao; Zhang, Shiyu; Zhou, Min
Abstract: 1-Naphthol is widely used as an intermediate in the plastics, dyes, fibers and rubbers production areas, leading to the increasing detection of 1-naphthol in the soil and water environment, which is of particular concern due to its acute toxicity and negative environmental impacts. Considering the high surface area and good stability of ZIFs (zeolitic imidazole frameworks) material, ZIF-67 (a representative cobalt-based ZIFs material) was synthesized and applied as an adsorbent for removal of 1-naphthol from aqueous solution. The obtained ZIF-67 was characterized by XRD, TEM, XPS, N2 physisorption and TG, and the adsorption isotherm, kinetics, and regeneration of the adsorbent were studied in detail. The adsorption of 1-naphthol on ZIF-67 followed a pseudo-second-order equation kinetics and fitted Langmuir adsorption model with a maximum adsorption capacity of 339 mg/g at 313 K, which is much higher than that of the common adsorbents reported such as activated carbon and carbon nanotubes et al. The solution pH was found to be an important factor influencing the adsorption process, which could be explained by the predominant mechanism controlling the process, i.e. electrostatic attraction. In addition, the ZIF-67 showed desirable reusability toward 1-naphthol removal from alkaline aqueous solution. Highlights: ZIF-67 was synthesized and applied as an adsorbent for 1-naphthol removal. High 1-naphthol adsorption capacity of 339 mg/g at 313 K was obtained by ZIF-67. Kinetics and thermodynamics of the 1-naphthol adsorption are investigated.